Design, Analysis and Optimization Using Solidwork Simulation of Chair Ladder - IDRIS, MOHD DANIAL FAYYADH BIN; Esa, Mohd Faizal (Progress in Engineering Application and Technology, 2021)
Chair Ladder is an idea of combining a chair and a ladder in one. Hence, it can help save money, time and energy. The design of Chair Ladder must can withstand a weight of 1500N.  The project involves two different object that is a chair. Its main characteristics are two pieces of sturdy material, linked at a 90 ° or slightly higher angle to each other, as the back and seat are typically attached to the four corners of the horizontal seat in turn to four legs or other parts of the underside of the seat attached to three legs or to a shaft around which a four-arm roller may be powerful enough to withstand the weight of a person sitting on the seat. Next, for climbing up or down, a ladder is a step consisting of two parallel members linked by rungs. It's an ascending stage that helps someone or something to scale the ladder. The simulation analysis is done using Solidwork software and tested using linear static analysis and drop test analysis. The result shown that the design can undergoes a force around 1500N on its seat and step ladder without being broken. Therefore, this design can achieve the objective stated.